Knowledge regarding prevention of child abuse among parents at selected rural area of Western Rajasthan - Yadav, Nisha; Kumari, Nirmala; ., Parmeshwari; ., Pooja; ., Pooja; Poonia, Pooja; Bairwa, Preeti Kumari; Vyas, Himanshu; T., Deviga (International Journal Of Community Medicine And Public Health, 2020)
Background: Child abuse is a kind of domestic violence that involves all forms of physical, emotional and sexual maltreatment and negligence of children under the age of 18 years which potentially or actually damages all aspects of their health. Child abuse is a global problem with serious lifelong consequences. In India the child abuse has not received enough attention. There have been few and irregular efforts to understand and address the problem. Aim was to assess the level of knowledge regarding prevention of child abuse among parents. Methods: Descriptive Survey design was used. The study population comprised of parents of children less than 18 years of age. A sample of 60 parents were selected by non-probability purposive sampling technique. A self-structured questionnaire was used to assess the knowledge regarding child abuse among parents. Informed consent was taken from each participant prior to data collection and descriptive and inferential statistics were used to analyse the data. Results: Majority of parents 60% had poor or fair level of knowledge, 39% had good knowledge whereas only 1.6% had excellent knowledge. There was a significant association between knowledge and age of mother at 0.02 level of significance. Conclusions: The finding of the study concluded that the knowledge regarding child abuse among parents was inadequate. Considering this aspects further awareness drives can be conducted to make the people alert about child abuse and its prevention.